Building complexity: Evaluating stone crab recruitment to novel engineered habitats in coastal North Carolina - Whitt, Dylan Kennedy (East Carolina University, 2025)
Living shorelines, which often include breakwaters constructed from novel engineered substrates, can provide structural complexity that may enhance habitat for fauna, yet relationships between specific design features and faunal recruitment remain poorly understood. This study evaluated how three proprietary breakwater substrates (Natrx Exoforms™, Oyster Catcher™, and QuickReef®) influenced stone crab (Menippe mercenaria) recruitment at newly installed living shorelines in coastal North Carolina. We evaluated habitat complexity via measurements of rugosity and interstitial space on each structure type and quantified stone crab abundances by deploying passive samplers adjacent to replicate breakwaters of each substrate type from April through September 2025. Although these substrates differed significantly in their complexity metrics, stone crab abundance and size were similar across Natrx Exoforms™ (N= 4.33 +/- 2.52 crabs, 67.99 +/- 33.54 mm carapace width), Oyster Catcher™, (N= 3 +/- 1 crabs, 89.42 +/- 16.42 mm carapace width and QuickReef®( N= 3 +/- 2 crabs, 75.29 +/- 26.88 mm carapace width). Previous studies have demonstrated that stone crabs experience size-specific habitat limitation and thus will recruit to habitats based on the size of the available refuge relative to carapace width. Our results suggest that the measured differences in habitat complexity across the breakwaters may not represent differences in the availability of size-appropriate refuges (i.e., burrows) for recruiting stone crabs. Future studies should evaluate stone crab recruitment over multiple years post-construction of novel substrates to assess whether colonization by other fauna (e.g., oysters) influences habitat selection by stone crabs.
Keywords: Biology, Ecology